Roadmap for Recognition of Coronary Surgery as a Subspecialty - Raja, Shahzad G. (British Journal of Healthcare and Medical Research, 2026)
Coronary artery bypass grafting (CABG) remains a cornerstone of cardiovascular surgery, yet coronary surgery has not been formally recognized as a distinct subspecialty despite its increasing technical complexity and impact on patient outcomes. As the risk profile of CABG patients continues to evolve—often characterized by advanced age, severe comorbidities, and prior interventions—off-pump coronary artery bypass grafting (OPCAB) has emerged as a preferred strategy for reducing surgical morbidity and improving recovery. Specialized expertise in coronary revascularization, including OPCAB and total arterial grafting techniques, has been shown to optimize long-term survival, reinforcing the need for dedicated training pathways. In addition to traditional approaches, minimally invasive techniques such as robotic-assisted CABG and hybrid revascularization strategies are increasingly recognized for their ability to reduce surgical trauma, enhance graft patency, and accelerate postoperative recovery. Despite these advancements, current cardiac surgical training lacks structured subspecialization in coronary surgery, limiting the widespread adoption and refinement of these techniques. The absence of formalized coronary surgery training contributes to variability in surgical expertise, influencing patient outcomes across institutions. This review outlines the imperative need for recognizing coronary surgery as a subspecialty, addressing key challenges such as institutional resistance, variability in case volume, and limited research on the long-term benefits of specialized coronary surgeons. It further proposes a structured framework for achieving recognition, including dedicated fellowship programs, standardized curricula emphasizing OPCAB and arterial grafting, accreditation mechanisms, and evidence-based guidelines. The integration of advanced imaging technologies and artificial intelligence-driven surgical planning also presents opportunities to enhance precision in coronary revascularization. Future research should focus on demonstrating the improved patient outcomes associated with specialized coronary surgeons, evaluating the cost-effectiveness of coronary surgery subspecialization, and refining minimally invasive CABG techniques through real-world evidence. Recognizing coronary surgery as an independent subspecialty could lead to enhanced surgical expertise, optimized revascularization strategies, and broader adoption of innovative techniques—ultimately improving long-term results for patients undergoing CABG.